2020
DOI: 10.1016/j.jaci.2020.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Type I IFN immunoprofiling in COVID-19 patients

Abstract: B enite, d the National Referee Centre for Rheumatic and AutoImmune and Systemic diseases in childrEn (RAISE), and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
241
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 249 publications
(265 citation statements)
references
References 6 publications
21
241
1
2
Order By: Relevance
“…Although there is conflicting data on the presence of an IFN gene signature (IGS) and whether SARS-CoV2 infection induces a robust IFN response (Blanco-Melo et al, 2020;Trouillet-Assant et al, 2020;Wei et al, 2020), we observed increased expression of Type I IFN genes (IFNA4, IFNA6, IFNA10) and significant enrichment of the common Type I and Type II IGS, including enrichment of IFNA2, IFNB1 and IFNG gene signatures specifically in the lung tissue ( Figure 2A&B). Furthermore, we detected increased expression of genes found to be important for the anti-viral innate immune response (IFIH1, DDX58, EIF2AK2, OAS2) and decreased expression of negative regulators of this response (IRF2BP1, SKIV2L) in both the lung and airway compartments ( Figure 2C) (Fischer et al, 2020).…”
Section: Covid-19 Patientsmentioning
confidence: 65%
“…Although there is conflicting data on the presence of an IFN gene signature (IGS) and whether SARS-CoV2 infection induces a robust IFN response (Blanco-Melo et al, 2020;Trouillet-Assant et al, 2020;Wei et al, 2020), we observed increased expression of Type I IFN genes (IFNA4, IFNA6, IFNA10) and significant enrichment of the common Type I and Type II IGS, including enrichment of IFNA2, IFNB1 and IFNG gene signatures specifically in the lung tissue ( Figure 2A&B). Furthermore, we detected increased expression of genes found to be important for the anti-viral innate immune response (IFIH1, DDX58, EIF2AK2, OAS2) and decreased expression of negative regulators of this response (IRF2BP1, SKIV2L) in both the lung and airway compartments ( Figure 2C) (Fischer et al, 2020).…”
Section: Covid-19 Patientsmentioning
confidence: 65%
“…Wei and colleagues demonstrated that genesfunctioning in viral defense, such as ISGs, are highly expressed inperipheral blood mononuclear cells of SARS-CoV-2 infectedindividuals requiring intensive care [16]. In one study, peak IFNα2levels occurred on days 8-10 of symptom onset and graduallydecreased over the following 2-3 weeks in critically ill adults [17].…”
Section: Resultsmentioning
confidence: 99%
“…Here we show that in-vitro, SARS-CoV2 PLpro was able to cleave IRF3 and validated that the effect could be observed in relevant virus infected cells ( Figure 5). Direct proteolytic cleavage of IRF3 may contribute to the reduction of type I interferon production observed in COVID19 patients [31,32]. TAB1 is part of the TAB1/2/3/TAK1 complex [70] that regulates the activity of TAK1 (TGFβ-activated kinase 1), in response to different stimuli including TGFβ, IL1, TNFα and upon viral and bacterial infection [71,72].…”
Section: Irf3 Tab1 and Nlrp12 Are Important Components That Drive Thmentioning
confidence: 99%
“…Structure-function correlative analysis followed by comparative alignment of IRF3 and NLRP12 homologs across relevant mammalian orders reveal the potential explanatory power of our findings. The cleavage of IRF3 could explain the enigmatically blunted type-I IFN response that have been noted in early studies of SARS-CoV-2 infections [31,32], while the NSP5 mediated cleavage of NLRP12 might explain the hyperinflammatory response linked to severe COVID-19 disease [33,34]. Indeed, the lack or presence of cognate cleavage motifs in IRF3 and NLRP12 homologs presents interesting correlations with the presentation of disease in animal models; our results will enable the development of more effective animal models for severe COVID-19.…”
Section: Introductionmentioning
confidence: 99%